Low temperature performance of proton irradiated strained SOI FinFET - Caparroz, L. F.V.; Bordallo, C. C.M.; Martino, J. A.; Simoen, E.; Claeys, C.; Agopian, P. G.D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper studies for the first time the low temperature characteristics of strained SOI FinFETs submitted to proton irradiation. Both types of transistors, nMOS and pMOS, were analyzed from room temperature down to 100K, focusing on the threshold voltage (VTH), subthreshold swing (SS), the Early voltage VEA and the intrinsic gain voltage (AV). The effects of strain techniques are also studied. The p-channel devices showed a greater immunity to radiation when looking at their digital parameters while nFinFETs had a better response to proton radiation from an analog parameters point of view.
Keywords: FinFET; low temperature; proton radiation; strained devices